Social and Interpersonal Dynamics in Pain We Don't Suffer Alone (Springer International Publishing, 2018)
This groundbreaking analysis moves our knowledge of pain and its effects from the biomedical model to one accounting for its complex psychosocial dimensions. Starting with its facial and physical display, pain is shown in its manifold social contexts-in the lifespan, in a family unit, expressed by a member of a gender and/or race-and as observed by others. These observations by caregivers and family are shown as vital to the social dynamic of pain-as observers react to sufferers' pain, and as these reactions affect those suffering. The book's findings should enhance practitioners' understanding of pain to develop more effective individualized treatments for clients' pain experience, and inspire researchers as well. Among the topics covered: Why do we care? Evolutionary mechanisms in the social dimension of pain. When, how, and why do we express pain? On the overlap between physical and social pain. Facing others in pain: why context matters. Caregiving impact upon sufferers' cognitive functioning. Targeting individual and interpersonal processes in therapeutic interventions for chronic pain. Social and Interpersonal Dynamics in Pain will be a valuable resource for clinicians who deal in pain practice and management, as well as for students and researchers interested in the social, interpersonal, and emotional variables that contribute to pain, the processes with which pain is associated, and the psychology of pain in general.